2023
DOI: 10.2174/1871527321666220329140804
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brain-Gut-Microbiota Axis in Depression: Emerging Therapeutic Avenues

Abstract: The human gut microbiota plays a significant role in the pathophysiology of central nervous system related diseases. Recent studies suggest correlations between the altered gut microbiota and major depressive disorder (MDD). It is proposed that normalization of the gut microbiota alleviates MDD. The imbalance of brain-gut-microbiota axis also results in dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. This imbalance has a crucial role in the pathogenesis of depression. Treatment strategies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…Several studies have revealed that the microbiota-gutbrain axis is important for regulating mood, behavior, and neuronal transmission in the brain, 113,114 and is associated with MDD. [115][116][117] Several studies have suggested that depression and gastrointestinal disorders are comorbid. 118,119 Some antidepressants can alleviate the symptoms of people suffering from irritable bowel syndrome and other related disorders.…”
Section: Microbiome-gut-brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that the microbiota-gutbrain axis is important for regulating mood, behavior, and neuronal transmission in the brain, 113,114 and is associated with MDD. [115][116][117] Several studies have suggested that depression and gastrointestinal disorders are comorbid. 118,119 Some antidepressants can alleviate the symptoms of people suffering from irritable bowel syndrome and other related disorders.…”
Section: Microbiome-gut-brain Axismentioning
confidence: 99%
“…Recent attention has been drawn to the microbiota–gut–brain axis owing to its potential to regulate brain activity. Several studies have revealed that the microbiota–gut–brain axis is important for regulating mood, behavior, and neuronal transmission in the brain, 113,114 and is associated with MDD 115–117 . Several studies have suggested that depression and gastrointestinal disorders are comorbid 118,119 .…”
Section: Pathological Mechanisms Of Depressionmentioning
confidence: 99%
“…development, function, mood and cognition may be influenced by the symbiotic flora (30). The gut microbiota and CNS are connected through multiple bidirectional pathways involving neural, endocrine, and immune signaling, and dysbiosis of the gut flora can cause psychiatric disorders, such as depression (31)(32)(33). Current studies suggest that intestinal flora dysbiosis can mediate depression by causing an inflammatory response (34,35).…”
Section: Intestinal Flora Dysbiosismentioning
confidence: 99%
“…The association between gut microbiota and psychiatric disorders has received increasing research attention ( Morais et al, 2021 ). Over the past decade, many studies have revealed that the gut microbiota is directly involved in the production of various neurotransmitters, such as gamma-aminobutyric acid (GABA), serotonin (5-HT), glutamate, and dopamine (DA) ( Bull-Larsen and Mohajeri, 2019 ; Altaib et al, 2021 ; Bhatt et al, 2022 ), which are closely associated with a number of psychiatric disorders, including TD ( Kanaan et al, 2017 ), ADHD ( Turna et al, 2020 ), OCD ( Simpson et al, 2021 ), and anxiety ( Ridaura and Belkaid, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The association between gut microbiota and psychiatric disorders has received increasing research attention (Morais et al, 2021). Over the past decade, many studies have revealed that the gut microbiota is directly involved in the production of various neurotransmitters, such as gamma-aminobutyric acid (GABA), serotonin (5-HT), glutamate, and dopamine (DA) (Bull-Larsen and Mohajeri, 2019;Altaib et al, 2021;Bhatt et al, 2022), which are closely associated with a number Abbreviations: TD, Tic disorder; DSM, Diagnostic and Statistical Manual of Mental Disorders; TS, Tourette syndrome; CTD, chronic motor or vocal tic disorder; PTD, provisional tic disorder; OCD, obsessive-compulsive disorder; ADHD, attention-deficit/hyperactivity disorder; GABA, gammaaminobutyric acid; 5-HT, serotonin; DA, glutamate and dopamine; FMT, fecal microbiota transplantation; HC, healthy control; NOS, Newcastle-Ottawa Scale; GSI, gastrointestinal severity index; DRA, dopamine receptor antagonists; YGTSS, Yale Global Tic Severity Scale; ASD, autism spectrum disorders; SCFA, short-chain fatty acid.…”
mentioning
confidence: 99%